A review of stingless bees' bioactivity in different parts of the world - Goh, Lucky Poh Wah; Roslina Jawan; Ainol Azifa Mohd Faik; Jualang Azlan Gansau (Carol Davila University Press, 2022)
Stingless bees, also known as meliponines, live in beehives. However, reports on the distribution of stingless bees are scattered, resulting in a lack of precision. Honey and propolis are the main components that can be harvested from their beehive, with a great commercial value of up to 610 million USD. Despite the enormous potential profits, discrepancies in their bioactivities have been observed worldwide, leading to a lack of confidence. Therefore, this review provided oversight on the potential of stingless bee products and highlighted the differences between stingless bees in Asia, Australia, Africa, and America. The bioactivity of stingless bee products is diverse and exhibits great potential as an antimicrobial agent or in various diseases such as diabetes, cardiovascular disease, cancers, and oral problems.